Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Pada Usaha Bubuk Kopi Lanang Suhang Desa Talang Pagar Agung Kecamatan Pajar Bulan Kabupaten Lahat - Titi Hasanah; Hestin Hestin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to determine and analyze the influence of product quality, the effect of promotion, the effect of product quality and promotion in determining purchasing decisions for lanang suhang coffee powder. in 2018 to 2019 the development of the Lanang Suhang coffee powder business increased by 10%. In this study, the researcher used descriptive research with a quantitative approach that basically could be used from one of the existing methods. This study uses a quantitative approach because the research data obtained using numbers and analysis using statistics. The results of the research, namely the partial (individual) test, showed that product quality had no positive and insignificant effect on purchasing decisions at the Lanang Suhang Coffee Powder Business, Talang Pagar Agung Village, Pajar Bulan District, while promotion had a positive and significant effect on purchasing decisions in the Powder Business. Lanang Suhang Coffee, Talang Pagar Agung Village, Pajar Bulan District, Lahat Regency and simultaneously has a positive and significant effect on purchasing decisions in the Lanang Suhang powder business, Pajar Bulan District, Lahat Regency. Keywords: Product Quality Promotion Purchase Decision.